Electrochemical writing on edible polysaccharide films for intelligent food packaging. (15th April 2018) - Wu, Si; Wang, Wenqi; Yan, Kun; Ding, Fuyuan; Shi, Xiaowen; Deng, Hongbing; Du, Yumin
Highlights: Novel electrochemical writing method on chitosan/agarose/ATH hydrogel is proposed. The writing can be repeatable on the hydrogel while fixed on dried film. The chitosan/agarose/ATH film can detect the spoilage of crucian fish. The film can be used as a multifunctional intelligent packaging material. Abstract: Polysaccharide films used as intelligent food packaging possess the advantages of renewability, safety and biodegradability. Printing on the polysaccharidic food packaging is challenging due to the high demand for edible-ink and the need for a suitable printing technique. In this work, we propose an electrochemical method for writing on polysaccharide film. Unlike conventional printing, this electrochemical writing process relies on the pH responsive color change of anthocyanin embedded in the chitosan/agarose hydrogel. By biasing a negative potential to a stainless wire (used as a pen) contacting the surface of the chitosan/agarose/ATH hydrogel, the locally generated pH change induced the color change of ATH and wrote programmed information on the hydrogel. We demonstrate the writing can be temporary in the hydrogel but stable when the hydrogel is dried. We further demonstrate that the written film is applicable for the detection of the spoilage of crucian fish. The reported electrochemical writing process provides a novel method for printing information on polysaccharide film and great potential for intelligent food packaging.